2023
DOI: 10.1055/a-1955-5297
|View full text |Cite
|
Sign up to set email alerts
|

The Aging Human Liver: The Weal and Woe of Evolutionary Legacy

Abstract: Aging is characterized by the progressive decline of biological integrity and its compensatory mechanisms as well as immunological dysregulation. This goes along with an increasing risk of frailty and disease. Against this background, we here specifically focus on the aging of the human liver. For the first time, we shed light on the intertwining evolutionary underpinnings of the liver’s declining regenerative capacity, the phenomenon of inflammaging, and the biotransformation cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 121 publications
(143 reference statements)
0
7
0
Order By: Relevance
“…Aging, a major risk factor for increased susceptibility to certain diseases, is characterized by a gradual physiological process that affects all systems of the body, including cells, tissues and organs, which ultimately leads to impaired biological function of the organism [ 33 ]. Various endogenous and exogenous factors, such as genetic makeup or dietary habits, also have a significant impact on individualized aging [ 34 ]. It has been reported that aging, particularly hepatic age, can promote the development of steatosis, non-alcoholic steatohepatitis (NASH) and hepatocellular carcinoma by reducing the regenerative capacity, biotransformation and increasing inflammation of the liver [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging, a major risk factor for increased susceptibility to certain diseases, is characterized by a gradual physiological process that affects all systems of the body, including cells, tissues and organs, which ultimately leads to impaired biological function of the organism [ 33 ]. Various endogenous and exogenous factors, such as genetic makeup or dietary habits, also have a significant impact on individualized aging [ 34 ]. It has been reported that aging, particularly hepatic age, can promote the development of steatosis, non-alcoholic steatohepatitis (NASH) and hepatocellular carcinoma by reducing the regenerative capacity, biotransformation and increasing inflammation of the liver [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various endogenous and exogenous factors, such as genetic makeup or dietary habits, also have a significant impact on individualized aging [ 34 ]. It has been reported that aging, particularly hepatic age, can promote the development of steatosis, non-alcoholic steatohepatitis (NASH) and hepatocellular carcinoma by reducing the regenerative capacity, biotransformation and increasing inflammation of the liver [ 34 ]. In a territory-wide retrospective cohort study, Zhang et al [ 35 ] found that most patients with NAFLD and T2DM developed liver-related events or cirrhosis after age 50, suggesting that aging is an independent and strong predictor of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, one might arguably include Nancy Leslie Rutherford Bucher (1913Bucher ( -2017 as another founding mother in this illustrious circle [11]. In 1964, she was the first to show that the most striking effect of aging on the liver is the decline of the organ's remarkable capacity to 'regenerate' (a process correctly termed 'compensatory hyperplasia') in the event of tissue loss [12].…”
Section: Memorable Originsmentioning
confidence: 99%
“…In 1964, she was the first to show that the most striking effect of aging on the liver is the decline of the organ's remarkable capacity to 'regenerate' (a process correctly termed 'compensatory hyperplasia') in the event of tissue loss [12]. Not only epistemologically, but also in terms of practical medical relevance, this decline must be viewed against an evolutionary background spanning eons that helps to explain aging-related hepatic and systemic pathological effects, which may lead to novel options for their antagonization [11,13].…”
Section: Memorable Originsmentioning
confidence: 99%
See 1 more Smart Citation